2008
DOI: 10.1002/cssc.200800140
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenolysis of Aromatic Ketones in Mixed Choline–Betainium Ionic Liquids

Abstract: The palladium-catalyzed hydrogenolysis of aromatic ketones to alkylbenzenes was studied in mixtures of ionic liquids to explore the promotional effect of these reaction media. Choline-based ionic liquids displayed complete miscibility with the aromatic ketone substrate at reaction temperature and a clear phase separation of the derived alkylbenzene product at room temperature. Selected ionic liquids were then assessed as reaction media in the hydrogenolysis of aromatic ketones over palladium catalysts. A binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…[23] One of the main challenges of using ILs as solvents is the poor solubility of hydrogen. [24] Thus, the ruthenium complex acts as a hydrogen carrier by forming hydride compounds. [23] Zhu et al have reported the use of an IL connected to an additional binding agent with a boronic acid-containing functional group for the stabilization of ruthenium nanoparticles as catalytically active species.…”
Section: Isosorbide Production From Biomassmentioning
confidence: 99%
“…[23] One of the main challenges of using ILs as solvents is the poor solubility of hydrogen. [24] Thus, the ruthenium complex acts as a hydrogen carrier by forming hydride compounds. [23] Zhu et al have reported the use of an IL connected to an additional binding agent with a boronic acid-containing functional group for the stabilization of ruthenium nanoparticles as catalytically active species.…”
Section: Isosorbide Production From Biomassmentioning
confidence: 99%
“…Avnir [7] once reported that the catalytic hydrogenolysis of aromatic ketones by a sol-gel entrapped combined Pd-[Rh(cod)Cl] 2 catalyst, however, the selectivity of hydrogenation reaction towards the alkylbenzenes is low and the aromatic rings were fully hydrogenated. The result that reported by Prof. De Vos [8] suggests that the mixed choline-betainium ionic liquids has promotional effect on the hydrogenolysis of aromatic ketones catalytic by Pd catalyst, the conversion of aromatic ketones and selectivity to alkylbenzenes were all improved.…”
Section: Introductionmentioning
confidence: 99%
“…To rationalize this result, one must realize that the solubility of hydrogen in www.chemsuschem.org many ionic liquids is generally much lower than in convenient solvents. [26,27] Thus, for many reported hydrogenations in ionic liquids, it is the low mole fraction of the substrate or product, rather than the high mole fraction of the ionic liquid itself, that is responsible for the hydrogen dissolution. In the present case, it is unlikely that the dissolved cellulose would generate a sufficient hydrogen dissolution in the ionic liquid for keeping Pt/C active.…”
Section: Resultsmentioning
confidence: 96%